Lack of active follow-up of cancer patients in Chennai, India: implications for population-based survival estimates. - Swaminathan R; Rama R; Shanta V (Bulletin of the World Health Organization, 2008)
OBJECTIVE: To measure the bias in absolute cancer survival estimates in the absence of active follow-up of cancer patients in developing countries. METHODS: Included in the study were all incident cases of the 10 most common cancers and corresponding subtypes plus all tobacco-related cancers not ranked among the top 10 that were registered in the population-based cancer registry in Chennai, India, during 1990-1999 and followed through 2001. Registered incident cases were first matched with those in the all-cause mortality database from the vital statistics division of the Corporation of Chennai. Unmatched incident cancer cases were then actively followed up to determine their survival status. Absolute survival was estimated by using an actuarial method and applying different assumptions regarding the survival status (alive/dead) of cases under passive and active follow-up. FINDINGS: Before active follow-up, matches between cases ranged from 20% to 66%, depending on the site of the primary tumour. Active follow-up of unmatched incident cases revealed that 15% to 43% had died by the end of the follow-up period, while the survival status of 4% to 38% remained unknown. Before active follow-up of cancer patients, 5-year absolute survival was estimated to be between 22% and 47% higher, than when conventional actuarial assumption methods were applied to cases that were lost to follow-up. The smallest survival estimates were obtained when cases lost to follow-up were excluded from the analysis. CONCLUSION: Under the conditions that prevail in India and other developing countries, active follow-up of cancer patients yields the most reliable estimates of cancer survival rates. Passive case follow-up alone or applying standard methods to estimate survival is likely to result in an upward bias.